2023
DOI: 10.1186/s12891-023-06630-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of musculoskeletal disorders and associated risk factors in canadian university students

Abstract: Background Musculoskeletal disorders (MSKDs) present a significant burden to health care systems worldwide. Evidence suggests that university students may have unique risk factors for developing MSKDs; however, research on the corresponding prevalence and risk factors of MSKDs in Canadian students is limited. Methods Using a multi-year cross-sectional survey, we aimed to understand the prevalence and risk factors of MSKDs in students at McMaster Un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Recent research has been focused on investigating various factors while adjusting the higher incidence of LBP in older adults and women, as previously revealed [40,41]. A study reported that adverse risk factors of LBP included characteristics of the individual, such as older age [10].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has been focused on investigating various factors while adjusting the higher incidence of LBP in older adults and women, as previously revealed [40,41]. A study reported that adverse risk factors of LBP included characteristics of the individual, such as older age [10].…”
Section: Discussionmentioning
confidence: 99%